2018
DOI: 10.1093/abm/kay069
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Discrimination Prospectively Predicts Blood Pressure Across 10 Years in Racially/Ethnically Diverse Midlife Women: Study of Women’s Health Across the Nation

Abstract: Background Interpersonal discrimination is linked to greater risk for cardiovascular disease (CVD) and this association varies by race/ethnicity. Purpose To examine whether exposure to everyday discrimination prospectively predicts elevated blood pressure (BP), whether this association differs by race/ethnicity, and is mediated by adiposity indices. Methods Using data for 2,180 self-identified White, Black, Chinese, Japanese, and Hispanic participants from the Study of Women’s Health Across the Nation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…It has been suggested that omitting coping as a key moderator may obscure associations between racial discrimination and adverse health outcomes; our finding supports this notion [27,50,69]. At the same time, our finding conflicts with work showing significant main associations between racial discrimination and high blood pressure or hypertension among African Americans [31,32,33,34,35,36]. Mixed findings may be related to sample differences or inconsistencies in measurement of the exposure and outcome, among other methodological distinctions [27,28,36,46,83].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It has been suggested that omitting coping as a key moderator may obscure associations between racial discrimination and adverse health outcomes; our finding supports this notion [27,50,69]. At the same time, our finding conflicts with work showing significant main associations between racial discrimination and high blood pressure or hypertension among African Americans [31,32,33,34,35,36]. Mixed findings may be related to sample differences or inconsistencies in measurement of the exposure and outcome, among other methodological distinctions [27,28,36,46,83].…”
Section: Discussionsupporting
confidence: 52%
“…However, despite what we know about the stressfulness of racial discrimination, and the role of stress in the pathogenesis of hypertension, findings of an association between self-reported discrimination and myriad cardiovascular indicators are mixed [23,25,26,28,29,30]. Some studies have demonstrated evidence of associations between general or racial discrimination and various cardiovascular outcomes among African Americans, including high blood pressure or hypertension [31,32,33,34,35,36], increased cardiovascular reactivity [37,38,39,40], and lower nocturnal blood pressure dipping [41], whereas others have shown null effects [24,42,43,44,45]. Moreover, rather than consistently showing a linear or dose-response relationship, previous literature has illustrated distinctive patterns of association between frequency of racial discrimination and cardiovascular and other stress-related outcomes among African Americans (e.g., J-shaped, U-shaped, inverse U-shaped, M-shaped) [34,35,36,43,46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…In the SWAN study, exposure to Everyday Discrimination predicted increases in SBP and DBP over 10 years of follow‐up, even after adjusting for known sociodemographic, behavioral, and medical risk factors. However, consistent across multiple racial groups, when a measure of adiposity (either waist circumference or BMI) was added to the model, the association was no longer significant …”
Section: Resultsmentioning
confidence: 99%
“…However, consistent across multiple racial groups, when a measure of adiposity (either waist circumference or BMI) was added to the model, the association was no longer significant. 47 Several recent studies have examined the association between discrimination and inflammation. Among African Americans in the MIDUS study, experiences of discrimination were associated with increased emotional dysregulation (venting and denial) and with increased biological dysregulation, as measured by increases in three indicators of inflammation (interleukin-6, e-selectin, and c-reactive protein).…”
Section: Discrimination and Physical Healthmentioning
confidence: 99%
“…Studies find evidence that racial-ethnic (Geronimus et al 2006; Rodriguez et al 2019) and socioeconomic (Seeman et al 2010) inequalities in allostatic load scores—an indicator of stress-mediated wear and tear across body systems—increase across young through middle adulthood, indicating the early onset of chronic diseases in disadvantaged populations that may lead to excess deaths, especially in medically underserved populations. In a 10-year prospective cohort study of midlife women, Moody et al (2018) found that everyday discrimination contributed to increased central adiposity and elevated blood pressure. Miller et al (2015) found that poor black youth in Georgia exhibiting higher self-control and academic resilience in the face of adversity show accelerated cellular aging compared to their peers.…”
Section: Discussionmentioning
confidence: 99%